Feeling of Insecurity and Level of Tolerance among University Students (Chittagong University Journal of Biological Sciences, 2024)
The purpose of the present study was to explore whether there is any relation between insecurity feeling and tolerance level of university students as a function of types of university, study year and family structure. This study was conducted on 240 respondents purposively selected from different areas of the Chittagong district. The Bangla version of Insecurity Questionnaire and Tolerance level scale used indicated that private university students showed more insecurity than public university students (F = 229.06, df = 1, 228, p < .001), First year students had more insecurity than Second-Fourth year and MS students (F = 15.04, df = 2, 228, p < .001). A significant interaction effect was found between types of university and study year (F = 04.04, df = 2, 228, p < .02) and types of university and family structure (F = 8.39, df = 1, 228, p < .01) in insecurity feeling. On the other hand, students in public universities showed more tolerance level than private university students (F = 341.78, df = 1, 228, p < .001), MS students had more tolerance level than First year and Second year to Fourth year students (F = 7.13, df = 2, 228, p